Equity and sustainability in the Anthropocene: a social–ecological systems perspective on their intertwined futures. (30th November 2018) - Leach, Melissa; Reyers, Belinda; Bai, Xuemei; Brondizio, Eduardo S.; Cook, Christina; Díaz, Sandra; Espindola, Giovana; Scobie, Michelle; Stafford-Smith, Mark; Subramanian, Suneetha M
Non-technical summary: It is no longer possible nor desirable to address the dual challenges of equity and sustainability separately. Instead, they require new thinking and approaches which recognize their interlinkages, as well as the multiple perspectives and dimensions involved. We illustrate how equity and sustainability are intertwined, and how a complex social–ecological systems lens brings together advances from across the social and natural sciences to show how (in)equity and (un)sustainability are produced by the interactions and dynamics of coupled social–ecological systems. This should help understand which possible pathways could lead to sustainable and fair futures. Technical summary: There is remarkably little work on the interlinkages between sustainability and equity. This paper proposes an interdisciplinary conceptual framework addressing these twin challenges in the context of the Anthropocene. It shows that both equity and sustainability need to be understood as multi-dimensional and from diverse perspectives, with acceptable standards in all defining a desirable and acceptable life support zone. It proposes a shift in focus from individual elements and interactions, to system level dynamics and behaviour, advancing a social–ecological systems perspective through which both equity and sustainability are understood as intertwined drivers and outcomes of coupled systems dynamics. Over time, such dynamics become part of pathways which may move outside, or potentially be steered within, a desirable zone of 'equitable sustainability'. Ten sets of 'interaction dynamics', involving different dimensions of equity and sustainability, are illustrated, along with a provisional categorization of their interrelationships and potential intervention points. The paper discusses their roles in transformational pathways towards equitable sustainability, highlighting the importance of cross-scale change shaped by politics and power. Further conceptual, empirical and transdisciplinary effort is now needed to enrich this framework and address a range of implied research and practice questions critical to shaping fair and sustainable futures.